PEKSANAAN ASAS PROPORSIONALITAS DALAM PEMBENTUKAN PERJANJIAN WARALABA VIDEO EZY DI JAKARTA - Jessica Amelinda*, Ery Agus Priyono, Budiharto (Diponegoro Law Journal, 2014)
Franchising is one of the alternative options to develop business rapidly because it is issuing capital, which is cheaper than expand the business with their own capital, but sometimes conflict happens between franchisor and franchisee on cooperation in franchising. The franchise agreement is a testament to the cooperation in the field of franchising, however there are several clauses in the franchise agreement that do not comply with the principle of proportionality, because in general, franchise agreement is a standard agreement which is the product of the principle of freedom of contract. Frequently, the debtor is in a weak position because it has a lower economic position than creditors. An agreement that has the principle of proportionality substance is an agreement that give rights, opportunities, and equal opportunity to the parties to determine the fair exchanges for both of them.The author examines the implementation or application of the proportionality principle in the formation of Video Ezy franchise agreement in Jakarta because the author found some clauses that are less in accordance with the principle of proportionality, especially regarding the rights and obligations of the parties as well as the distribution of profits and fees. In examining the agreement, the author refers to Kitab Undang-Undang Hukum Perdata, Peraturan Pemerintah Nomor 42 Tahun 2007 about Franchise, Permendag Nomor 53 Tahun 2012 about Franchise Operation. The Keywords:  Principle of Proportionality and Franchise Agreement